Open Model for Independent Assessment of Digital Economy Competencies - V. Yu. Grigorev (Управленческое консультирование)
The article describes an open model for the independent assessment of the competencies of the digital economy developed and implemented by the Russian Academy of National Economy and Civil Service under the President of the Russian Federation (RANEPA)